The Facts about Mothballs - Fred Fishel (EDIS, 2014)
Mothballs, moth flakes, crystals, and bars are insecticides that are formulated as solids. Naphthalene and paradichlorobenzene, the active ingredients in mothballs, are registered as pesticides. As such, their label directions carry the force of the law, including use intent and the sites where they may legally be used. They can harm people, pets, or wildlife that may touch or eat the mothballs or that may breathe the vapors. This 3-page fact sheet was written by Fred Fishel and published by the UF Department of Agronomy, December 2014.